2018
DOI: 10.2147/cia.s156208
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the CHADS<sub>2</sub> and R<sub>2</sub>CHADS<sub>2</sub> scores for prognostic stratification in patients with coronary artery disease

Abstract: ObjectiveThe current risk model for long-term prediction in coronary artery disease (CAD) is complicated, while a simple useful model is still lacking. We aim to investigate if CHADS2 and R2CHADS2 scores could predict long-term outcome for patients with CAD.Patients and methodsWe enrolled 3,700 patients with CAD between November 2010 and September 2014 at the Department of Cardiology from Chinese PLA General Hospital. The CHADS2 and R2CHADS2 scores were calculated. All cases were followed to track the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…1) (p = 0.003). These findings may support the previous findings that a high CHADS 2 score has been proven to be a predictor of cardiovascular/cerebrovascular events in patients with documented CAD [4,5]. Moreover, it has been reported that approximately 75% of culprit Fig.…”
Section: Detection Of Myocardial Ischemia By Cardiac Ct Scans For Rfcsupporting
confidence: 91%
See 1 more Smart Citation
“…1) (p = 0.003). These findings may support the previous findings that a high CHADS 2 score has been proven to be a predictor of cardiovascular/cerebrovascular events in patients with documented CAD [4,5]. Moreover, it has been reported that approximately 75% of culprit Fig.…”
Section: Detection Of Myocardial Ischemia By Cardiac Ct Scans For Rfcsupporting
confidence: 91%
“…1 3 [2], but also a new onset of AF [3]. Moreover, the CHADS 2 score is constructed by risk factors of coronary artery disease (CAD), and has also been reported as a predictor of cardiovascular/cerebrovascular events in patients with CAD without AF [4,5]. The close relationship between AF and CAD has been reported [6], and that (1) the prevalence of CAD detected by coronary computed tomography (CT) is significantly higher in patients with AF than in those without [7], and (2) coronary angiography (CAG) can detect coronary narrowing (≥ 50%) in patients with AF who undergo RFCA of AF [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, CHA 2 DS 2 -VASc score had recently become a more useful score and outperformed CHADS 2 score for prediction of stroke and systemic embolization 12 , 14 . In addition, both of CHADS 2 and CHA 2 DS 2 -VASc scores were also used to predict CV outcomes in non-AF patients 9 11 , 15 17 . Chen et al reported that CHADS 2 and CHA 2 DS 2 -VASc scores could be used to predict 1-year all-cause mortality in patients with systolic heart failure 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In AF patients, there is a strong association between the CHADS 2 score and the annual risk of stroke 7 , 8 . In addition, CHADS 2 score was used to predict CV outcomes in the patients without AF 9 11 . Nevertheless, in recent years, CHA 2 DS 2 -VASc score has become a more useful score than CHADS 2 score for prediction of stroke and systemic embolization in AF patients 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…International Publisher used to predict CV outcomes in the patients without AF [17][18][19][20][21][22][23][24][25]. However, there was no literature discussing about the usefulness of CHADS 2 , R 2 CHADS 2 and CHA 2 DS 2 -VASc score for CV and all-cause mortality prediction in the patients with abnormal low and high ABI.…”
Section: Ivyspringmentioning
confidence: 99%